Estudo comparativo da rigidez arterial central em idosos com doença arterial coronariana grave e não grave - Lima, Damianna Rodrigues Alves Resende Teixeira (2020)
Introduction: Cardiovascular diseases are currently the leading cause of death worldwide; in 2015, it was estimated that 17.7 million people died from cardiovascular disease, representing 31% of all deaths worldwide. With ageing, systolic blood pressure (SBP) rises, and diastolic blood pressure (DBP) decreases, producing an enlarged pulse pressure (PP) due to arterial stiffness. Objective: This study aimed to compare the arterial stiffness of elderly patients with severe coronary artery disease (CAD) who underwent coronary angioplasty (group 1) with those who presented with CAD but did not require this procedure (group 0). Methods: This was a cross-sectional study in which 55 patients aged over 60 years who underwent cineangiographic examination and applanation tonometry to determine the carotid-femoral pulse wave velocity (c-fPWV) were selected. Participants were divided into two groups: group 0 (n = 21) and group 1 (n = 34). Results: In the comparative analysis, the c-fPWV was not different between the groups (group 0: 10.16 ± 0.49 m/s vs group 1: 9.5 ± 0.37 m/s). In the multivariate analysis with c-fPWV as the dependent variable and blood pressure values as independent variables, it was observed that for both groups, only the mean brachial systolic pressure (PSb) was significant: group 0 (β = 0.0676, p = 0.0183) and group 1 (β = 0.0246, p = 0.0172). Conclusion: Central arterial stiffness in elderly patients with severe and non-severe CAD is similar. Brachial systolic pressure seems to be the main determinant of c-fPWV in both groups.